Modern murders : the turn-of-the-century's backlash against melodramatic and sensational representations of murder, 1880-1914 /: the turn-of-the-century's backlash against melodramatic and sensational representations of murder, 1880-1914. (2023) - Michael-Berger, Lee
No abstract available